Ekspresi Protein HER-2/neu pada Berbagai Tipe Karsinoma Ovarium - Barliana Barliana; Faroek Hoesin; Dyah Fauziah (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2014)
Background HER-2/neu is second family of epidermal growth factor receptor (EGFR). Amplification of HER-2/neu gene presented in some carcinoma, especially breast carcinoma. Due to increasing incidency of ovarian carcinoma and its poor prognosis because of chemoresistancy, a study on HER-2/neu expression on ovarian carcinoma is conducted. Methods An observasional analytic design with cross sectional approach. Population and samples were paraffin blocks of many type ovarian carcinoma from archives in the Laboratory of Anatomical Pathology of Dr. Soetomo General Hospital, during January-December 2012. Fourty seven samples were obtained and stained with HER-2/neu antibody. HER-2/neu expression assessed by semiquantitative gradation of intensity. Difference of HER-2/neu expression in many type ovarian carcinoma was analyzed with Chi-Square test by probabilitas exact . Results There were 47 cases with mean age 48.51 years (range 19-68 years). Fourteen cases (29.8%) showed HER-2/neu overexpression (score 3+), Statistical analysis showed significant difference of HER-2/neu expression in ovarian carcinoma (p=0.000; coefficient contingency = 0.606). It was showed musinous and clear cell type had more overexpression of HER-2/neu. Conclusion There was HER-2/neu overexpression in ovarian carcinoma especially in mucinous and clear cell type. Key words: clear cell, endometrioid, HER-2/neu, mucinous, ovarian carcinoma, serous.